Morphological and molecular characterization of potential amnesic shellfish poisoning toxin-producing diatom Pseudo-nitzschia (bacillariophyeae) from Malaysia - Lim, Hong Chang. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The genus Pseudo-nitzschia is one of the most well studied marine diatoms as fifteen of the species are known tp produce the neurotoxin, domoic acid (DA) that is responsible for Amnesic shellfish Poisoning (ASP). Thus far, little attention is given to the distribution of Pseudo-nitzchia spp. In Malaysia. In this study, Three species of Pseudo-nitzchia were identified as P.pungens, P. brasiliana and P. dolorosa based on detailed ultrastructure under light and electron microscopy. species identification was supported by LSU rDNA phylogenetic analyses. The application of sequence-structure alignment based on the seconf internal transcribed spacer (ITS2) RNA transcript was also inferred to improve the phylogeny which allows comparisons at deeper taxanomic levels.